Assessment of the Effect of Rehmannia glutinosa Leaf Extract in Maintaining Skin Health: A Proof-of-Concept, Double-Blind, Randomized, Placebo-Controlled Clinical Trial - Srivastava S; Huang SF; Jagtap MS (Dove Medical Press, 2024)
Shalini Srivastava,1 Shu Fen Huang,2 Manjiri S Jagtap3 1Department of Clinical Development and Strategy, Vedic Lifesciences Pvt. Ltd., Andheri West, Mumbai, Maharashtra, India; 2Department of Biochemistry, NuLiv Holding Inc., Taipei City, Taiwan (Republic of China); 3Skin Cure n Care Clinic, Thane, Maharashtra, IndiaCorrespondence: Shalini Srivastava, Department of Clinical Development and Strategy, Vedic Lifesciences Pvt. Ltd., Morya House, 118-B, Off Link Road, Andheri West, Mumbai, Maharashtra, 400053, India, Tel +91-9619477885, Email shalini.s@vediclifesciences.comPurpose: A double-blind, placebo-controlled, randomized, proof-of-concept trial aimed to evaluate the efficacy and safety of VerbasnolTM [Rehmannia glutinosa Libosch leaf-based extract (RGLE)] in females, with moderate to severe acne vulgaris.Participants and Methods: Twenty-two females aged 18 to 35 years having moderate to severe acne with Global Acne Grading System (GAGS) scores of 19 to 38 were included in the study and were randomized in a 1:1 ratio to receive either one capsule (100 mg/day) of RGLE or placebo orally after breakfast for 56 days. The primary outcome was a change in acne severity measured by the GAGS compared to the placebo on day 56. The secondary outcomes were changes in the number of inflammatory acne lesions, facial sebum secretion, quality of life, local pain and itching, skin wrinkle severity, and other skin characteristics, including radiance, luminosity, smoothness, texture, firmness, and hydration. Additionally, the percentage of responders and global tolerability and efficacy were evaluated.Results: The mean GAGS score was reduced by 21.72% and 14.20% on day 28 in RGLE (n=10) and placebo groups (n=12), respectively, which further reduced in both groups on day 56. The RGLE group reported better improvement in other skin characteristics on day 56. No safety or tolerability concerns were reported for the extract. RGLE reduced acne and improved the skin quality in females compared to placebo as early as 28 days of supplementation.Conclusion: RGLE supplementation at a dose of 100 mg/day has provided a clinically relevant decrease in acne severity and improved the skin hydration and quality of life of the participants with acne after 56 days of dose administration.Keywords: acne, healthy skin, herbal extract, Rehmannia glutinosa, quality of life